Prophylactic barrage laser in patients with previous vitreous loss during cataract surgery: a randomized clinical trial - Ehsan Namvar; Mostafa Abuali; Mohammad Amin Setoodehmanesh; Mehdi Moalem (BMC Ophthalmology)
Abstract Background One of the significant challenges that can arise during cataract surgery is the occurrence of posterior capsule rupture (PCR) and vitreous loss. It may result in different complications including cystoid macular edema, endophthalmitis, glaucoma, and considerably retinal detachment which consequently contributes to poor functional outcomes. Methods This study was a prospective double blinded randomized clinical trial including 42 patients with previous complicated cataract surgery including posterior capsular rupture and consequently vitreous loss that anterior vitrectomy was done for them. The patients were randomly categorized in to two groups by simple randomization. One group (25 patients) received sham laser and the other group (17 patients) received prophylactic 360° barrage laser 4 weeks after cataract surgery. After eighteen months, rate of retinal detachment was compared between two groups. Results In terms of gender, age, axial length, maturity, pseudophakia v/s aphakia, type of IOL and type of cataract surgery, there was no statistically significant difference between intervention and control groups. Distribution of RRD was clinically different between 2 groups (intervention and control group). In addition, there was a statistically significant difference between the rate of RRD in control group (non-laser patients) and normal population (0.08 vs. 0.0001). (P-value < 0.001). Conclusion Prophylactic barrage laser might be a useful intervention in eyes with posterior capsule rupture and vitreous loss during cataract surgery to prevent rhegmatogenous retinal detachment. However, further studies with larger sample sizes are indicated. Trial registration Iranian Clinical Trial Registry: IRCT20201120049450N2, Registered 13 Jul 2023, https://irct.behdasht.gov.ir .